Geraldo de Barros: o design e a arte concreta no Brasil - Valente, Carlos Eduardo da Silva (1998)
This paper aims at showing how the Concrete Art provided the development of the design in Brazil, specially graphic design. The Concrete Art contributed for the development of the design within inheritance of wood work, the modern artists and architects and the publicity. This will be proved through the artist and designer Geraldo de Barros. This study will show the definition and historic of design, besides the Concret Moviment in Brazil and his effects.